Efectividad del método blue-intensity en cordia alliodora (ruiz & pav.) oken. de la quinta experimental el Padmi, provincia de Zamora Chinchipe - Muñoz Chamba, Darwin Israel (2021)
Blue intensity is a relatively new methodology based on digital analysis of scanned images through a specialized software this methodology is related with the maximum Wood density of each individual tree ring. Lately it's been applied to conifer species for paleoclimatic studies. Nevertheless, the application of this method in broadleaf species has been void. Thus, in this investigation we applied Blue intensity methodology in Cordia alliodora (Ruiz & Pav.) Oken. with scanned images in a resolution of 2400 dpi of 69 increment cores already crossdated from 19 individual. The generation of Blue intensity information was performed using specialized software called CooRecorder version 7.8, in order to verify its efficacy in broadleaved species and establish a relationship with ring width. The results showed that the method is effective in determining ring density. The software only took into account the fiber bands for the measurement and the vessels were marked white, which does not influence the measurements, it was also observed that the values with the highest reflectance are from those rings located in the sapwood area, and these values decrease as they approach the heartwood zone. The relationship of Blue intensity and Ring width, taking into account the age of the trees was high (r = 0.69) and in a chronological analysis the relationship was (r = 0.59), both relationships were made without taking into account the first and last year, because the correlation in these years was weak, possibly due to the number of samples, which in these years was lower. The results of this study were positive and encouraging, this offers possibilities for future paleoclimatic reconstructions. However, this is an initial study and further research is needed to verify the application of the method to other tropical species. Key words: Blue-intensity, Tropics, Cordia alliodora (Ruiz & Pav.) Oken., Ring density, dendrochronology